Preventing Opioid-Related Harms in the Construction Industry. (November 2021) - Roelofs, Cora; Rodman, Christopher; Rinehart, Richard; Cain, Chris Trahan
The construction sector has been hit hard by the opioid crisis. We describe CPWR—The Center for Construction Research and Training's recent efforts to address the challenges of opioid use in the construction industry. With support and guidance from the North America's Building Trades Unions Opioid Task Force, CPWR undertook three projects to promote prevention and best practices for struggling construction workers. The first project focused on recommendations for communications that reframe stigmatizing narratives into effective messages about prevention solutions. The second project refined and distributed a one-hour construction worker opioid hazard awareness training module. The third project assessed opportunities and barriers for the expansion and improvement of existing union peer support programs to support workers through treatment and recovery. Additional resources, such as opioid hazard tool box talks, to help reverse the impact on the sector are also described.